Improvement of tribological characteristics of coupling parts "shaft-sleeve" with polymer and polymer-composite materials - Aulin, V.V.; Lysenko, S.V.; Hrynkiv, A.V.; Pashynskyi, M.V. (Problems of Tribology, 2022)
The article provides an analytical justification of the flow of tribological processes of coupling of "shaft-sleeve" parts, which simulates the functioning of sliding bearings and cylindrical joints of machines. The main attention is paid to such characteristics as contact pressure, static and dynamic forces, the criterion of the product of the total pressure on the sliding speed, the work of friction forces and its transition into thermal energy in the friction zone for polymer (based on polyamide P-68) and polymer-composite coatings (based on P-68 with kaolin filler) on the working surfaces of the parts. A comparative analysis of the functioning and tribological characteristics of the couplings of parts without coatings is presented. Experimentally, on the basis of tests of samples on the MИ-1M friction machine, a significant reduction in wear and an increase in the relative wear resistance of samples with polymer-composite coatings in the modes of friction without lubrication (by 1.3...1.4 times) and marginal friction (in 1.2...1.3 times), as well as a decrease in the temperature in the friction zone (365 K and 347 K) compared to the polymer coating.